Application of response surface methodology (Rsm) for optimizing production condition for removalof Pb (Ii) and Cu (Ii) onto kenaf fiber based activated carbon - Chowdhury, Z.Z. (2012)
This research aims to find out the feasibility of preparing kenaf fiber based carbon for removal of divalent cations of Pb (II) and Cu (II) from waste water. Activated carbon was prepared by using physiochemical activation method which involves two step of potassium hydroxide impregnation (KOH) with carbon dioxide activation of the semi carbonized char. The effects of three preparation variables; temperature (500-700°C), time (1-3 h) and Impregnation Ratio (IR) by using KOH (1-3) on the removal percentage of Pb (II) and Cu (II) ions were investigated by using Design of Experiment (DOE). Quadratic models were developed to correlate activated carbon preparation variables from kenaf fibers with the two responses by applying Central Composite Design (CCD). Experimental data were analysed by using analysis of variance (ANOVA) and the most influential factor on each experimental design response was identified. Process optimization was done by validating both the model to obtain maximum removal efficiency with possible maximum yield of activated carbon. © Maxwell Scientific Organization, 2012.